Crise do estado e da democracia no contexto da globalização. (2019)
The article intends to present how the phenomenon of globalization impacts the State and democracy putting them into crisis. In relation to globalization, its relation with economy, political organization and culture will be analyzed. The fact that seems to be unquestionable is that the society as a whole is involved in this process of globalization and in an increasingly intense way. The text is divided into four parts, three of which are directly related to globalization and a fourth one dealing with the impact of globalization on the State and on democracy. Globalization undermines the traditional idea of state based on territory, people and sovereignty, and therefore, seeks a new format that fits the reality of globalization. Regarding democracy, the impact is on the idea of representation. That is, the crisis is not of democracy, but of representation.